Talak Perspektif Syekh Qutbhi Dan Syekh Quraish Shihab - Muhammad Jufri; Rikki Arisandi (Mabahits : Jurnal Hukum Keluarga Islam, 2021)
The negative stigma which states that Muslims are anti-Pancasila, radical and intolerant is a problem now faced by Muslims in Indonesia. The sacrifices of Islamic groups when formulating Pancasila seem to be forgotten by some Indonesian people today. Their tolerance for accepting the abolition of the seven words in the Jakarta Charter with the aim of maintaining the integrity of the Unitary State of the Republic of Indonesia (NKRI) seems to have no value. Therefore, this article aims to highlight the role of Islamic groups (ulama) in the formulation of Pancasila and the reference for acceptance of Islamic groups (Ulama) to erase the seven words in the Jakarta Charter. This research is a historical research using a descriptive qualitative approach. The data collection technique used is a literature review by simplifying the data into a form that is easier to read as a form of analysis. So a number of results can be found. First, that the role of Islamic groups in the formulation of Pancasila is very large, this is reflected in their proposals during the formulation session. Second, the reference for Islamic groups (Ulama) to accept the abolition of the seven words in the Jakarta Charter is Sadd Dzari'ah, namely closing the means/roads to something bad. Third, as a result of the abolition, Muslims have lost their constitutional rights to carry out Islamic law properly and calmly.